Molecular characterization and expression profiles of two interleukin genes IL-8 and IL-10 in Pacific cod (Gadus macrocephalus) - Chen Jiang; Xu Yang; Hao Xu; Mingguang Mao; Bing Chen; Zhen Yang; Yude Guan; He Wang (Aquaculture Reports, 2021)
During the early development of the Pacific cod, high mortality due to viral infection is observed. To demonstrate the immune responses activated in Pacific cod during this critical period, two cytokines, the proinflammatory cytokine interleukin-8 (IL-8) and the anti-inflammatory cytokine interleukin-10 (IL-10), were identified and characterized in this study. The cDNA of IL-8 was 1047 bp in length, containing an ORF of 297 bp that encoded a 98 aa protein, whereas the IL-10 cDNA sequence consisted of 856 bp that harbored a 537 bp ORF encoding a 178 aa protein. Pairwise comparison and phylogenetic analysis of the two genes clearly demonstrated their close relationships with their counterparts in the Atlantic cod. Constitutive expression was detected in eight tested tissues; the transcription of both genes was observed during the critical period of the early developmental stage in Pacific cod, and their expression levels dramatically increased following poly I:C stimulation of larvae at 12 days post-hatching (dph). Taken together, these results suggested that IL-8 and IL-10 may be involved in the inflammatory responses of Pacific cod.